Pengaruh Minat Belajar Terhadap Prestasi Siswa Kelas V Sd N 1 Gemblegan Tahun Pelajaran 2023/2024 - Tri Oktavia Pramita Sari; Sri Suwartini; Isna Rahmawati (CV. ITTC INDONESIA, 2024)
This research aims to explore the influence of interest in learning on student achievement in natural and social science subjects in class V of SD N 1 Gemblegan for the 2023/2024 academic year. The research method used is quantitative correlation, which describes the relationship between the variables studied. Data for this research was obtained through questionnaire techniques to measure students' interest in learning, tests to measure learning achievement, and also through documentation. The research results show that there is a significant and positive influence between interest in learning and student achievement in natural and social science subjects in class V of SD N 1 Gemblegan for the 2023/2024 academic year. This is reinforced by the tcount value which reaches 4.138, which is greater than the t table of 2.093. This means that the accepted hypothesis is acceptable, indicating that interest in learning has an influence on student achievement in this subject. In addition, the coefficient of determination (R Square) of 48.8% indicates that the independent variable, namely interest in learning, is able to explain most of the variability in student learning achievement, while friendship (73.6%) can be explained by other variables that are not included. in this research.